A new technology using a customized 3D printed fixator to assist fracture reduction and fixation: Technical note. Issue 4 (30th April 2021) - Wu, Jianghong; Zhou, Panyu; Zhang, Yuntong; Xiao, Liang; Li, Lei; Xu, Shuogui
Abstract: Background: Poor reduction can lead to complications such as deformity and delayed fracture healing. We introduce a 3D printed external fixator technology that can assist in fracture reduction and fixation. Methods: A fractured long bone was first fixed by a temporary external fixator and then scanned with computed tomography. Three‐dimensional reconstruction of the contour and bone fragments of the affected limb was performed using Mimics software, and the fracture reduction was simulated. Subsequently, data were imported into SolidWorks software for customized external fixator design and 3D printing. Through the precise assembly of the 3D printed external fixator and external fixation pins, automatic fracture reduction. Results: The patient's fractures were well reduced, firmly fixed, and the postoperative fractures healed well with no complications. Conclusion: The technique we introduce not only assists in fracture reduction for temporary external fixation but can also be used as a definitive treatment for long bone fractures.